Frontiers in Fusion Research Physics and Fusion - Kikuchi, Mitsuru (Springer eBooks., 2011)
Frontiers in Fusion Research provides a systematic overview of the latest physical principles of fusion and plasma confinement. It is primarily devoted to the principle of magnetic plasma confinement, that has been systematized through 50 years of fusion research. Frontiers in Fusion Research begins with an introduction to the study of plasma, discussing the astronomical birth of hydrogen energy and the beginnings of human attempts to harness the Sun?s energy for use on Earth. It moves on to chapters that cover a variety of topics such as: charged particle motion, plasma kinetic theory, ? wave dynamics, ? force equilibrium, and ? plasma turbulence. The final part of the book describes the characteristics of fusion as a source of energy and examines the current status of this particular field of research. Anyone with a grasp of basic quantum and analytical mechanics, especially physicists and researchers from a range of different backgrounds, may find Frontiers in Fusion Research an interesting and informative guide to the physics of magnetic confinement.